Meaning in Life and Coping With Everyday Stressors. (March 2023) - Ward, Sarah; Womick, Jake; Titova, Liudmila; King, Laura
Meaning in life (MIL) has been proposed to improve coping and resilience. Yet MIL's association with coping has primarily been investigated in the context of extreme stressors and trauma, often using varied measures of MIL. Is MIL associated with varied coping strategies, coping self-efficacy, and distress in relation to commonly experienced, everyday challenges? Using diverse methodological designs, five studies (total N = 1, 646) investigated the association between MIL and coping strategies/appraisals pertaining to varied challenging, stressful events. Across recalled (Studies 1 and 2), anticipated (Study 3), and experienced stressors (Studies 3–5), MIL was consistently associated with positive reinterpretation, proactive planning, coping self-efficacy, and stress. MIL was inconsistently related to threat/emotion-coping.